M’S ID, Ego, and Superego in Film How to Make Millions Before Grandma Dies - Muyassaroh; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research explores the psychological conflict experienced by the main character, M, in the Thai film How to Make Millions Before Grandma Dies (2024). This study uses Sigmund Freud's psychoanalytic theory, specifically the concepts of id, ego, and superego, to analyze M's inner transformation. At the beginning of the story, M is driven by a personal desire to inherit from his grandmother. However, as time goes by, he experiences emotional changes that make him face an inner conflict between his ambition and his growing moral awareness, as well as an increasingly strong emotional bond. The cultural value of filial piety in Thai society plays an important role in this process, as it helps shape M's moral awareness and the development of his superego structure. Using qualitative descriptive methods, this study identifies how M's psychological conflict is reflected through his actions, expressions, and developing relationship with his grandmother. The results show that the character's internal conflict undergoes a transition from id to the ego, followed by superego, which is influenced by cultural values. This research contributes to a deeper understanding of character development in Southeast Asian cinema by combining Freud's psychoanalytic theory with the local moral framework of filial piety values.